2013
DOI: 10.1136/bmjspcare-2012-000419
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and suffering of caring for people with primary malignant glioma: qualitative perspectives on improving current supportive and palliative care practices

Abstract: The results of this study shed new light on providing timely information and palliative care to support carers. We call for health services to reconsider the current medical model for this patient group, where patients are the centre of care, information and support, towards a more collaborative model which places carers and patients into a partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 31 publications
1
88
0
Order By: Relevance
“…Although most participants in this study found ACP acceptable to discuss, which is consistent with other previous qualitative studies [24,25], most participants in this study had variable views on when the implementation of the ACP process should occur. Illness uncertainty sometimes justified its delay or BT patients' perceived good health and treatment progress.…”
Section: Discussionsupporting
confidence: 88%
“…Although most participants in this study found ACP acceptable to discuss, which is consistent with other previous qualitative studies [24,25], most participants in this study had variable views on when the implementation of the ACP process should occur. Illness uncertainty sometimes justified its delay or BT patients' perceived good health and treatment progress.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that brain cancer produces a high degree of symptom burden for patients and caregivers 36,37 , with caregivers reporting poor physical and emotional health, career sacrifices, monetary losses, and immense strain 36,37 . Currently, the provision of support and coping therapy for informal carers is lacking, and that lack in turn contributes to a worsening of their stresses 34,36,38,39 . Patients are panicked and uncomfortable with the idea of shifting the type of relationship they have with their loved ones, and they do not want to impose that type of strenuous responsibility on them.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review it was suggested that promoting healthy family dynamics through psychosocial treatment of both patient and caregiver helps caregivers cope, and may also be beneficial for the patient's (emotional) health (Hopkinson et al 2012). In providing support, it is important to realise that the needs of caregivers may differ from patients' needs at various time points (Collins et al 2014). …”
Section: Supportive Care and Interventions For Family Caregiversmentioning
confidence: 99%
“…A conversation on EOL, if ill-executed or poorly timed, could hinder this. However, in hindsight, many caregivers would have liked to be better informed as reported in a retrospective qualitative study (Collins et al 2014). The optimal timing to initiate conversation on EOL may be different for each patient-caregiver dyad, and is largely up to the treatment team to determine.…”
mentioning
confidence: 99%
See 1 more Smart Citation